Molecular Docking and QSAR Analysis of N-(Ethylcarbamothioyl)benzamide Derivatives as Dual Estrogen-Alpha and Progesterone Receptors Inhibitor for Breast Cancer - Anung Kustriyani; Bambang Tri Purwanto; Tri Widiandani; Khoirunnisa Muslimawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Luminal A subtype breast cancer is the most prevalent disease suffered by women, characterized by the presence of positive hormone receptors in the form of estrogen and progesterone. Thiourea derivatives have been shown to exhibit cytotoxicity against breast cancer cells in silico across multiple receptor targets. The purpose of this study was to determine the binding energy and QSAR equation of N-(Ethylcarbamothioyl)benzamide derivatives in silico. Molecular docking of the compounds was performed using AutoDockTools-1.5.7 with estrogen-α (PDB ID: 3ERT) and progesterone (PDB ID: 2OVM) receptor targets. The results showed that the compound 4-(benzyloxy)-N-(ethylcarbamothioyl)benzamide had the smallest free energy of binding (∆G) and Ki on estrogen-α and progesterone receptor of -7.13 kcal/mol and 5.96 μM and -8.04 kcal/mol and 1.27 μM, respectively. The best QSAR equation for estrogen-α receptor is ∆G = 0.465 (LogP)2 - 2.276 logP + 0.311 ELUMO - 0.091 MR + 5.075 (R = 0.914, α <0.001, F = 16.595 and SE = 0.41331) and progesterone receptor is ∆G = -0.058 (LogP)2 - 0.033 tPSA + 0.011 Etot - 0.08 MR + 1.683 (R = 0.92, α <0.001, F = 18.028 and SE = 0.37388). The QSAR equation is statistically significant if the R-squared value approaches 1, significance (α <0.05), Fcount > Ftable, and the smallest standard deviation (s). The predicted physicochemical properties that influence cytotoxic activity at the estrogen-α receptor are lipophilic (logP), electronic (ELUMO), and steric (MR). In contrast, those at the progesterone receptor are lipophilic (tPSA), electronic (Etot), and steric (MR).